Keep America Christian (and White): Christian Nationalism, Fear of Ethnoracial Outsiders, and Intention to Vote for Donald Trump in the 2020 Presidential Election. (14th May 2020) - Baker, Joseph O; Perry, Samuel L; Whitehead, Andrew L
Abstract: Some of the strongest predictors of voting for Donald Trump in the 2016 presidential election were Christian nationalism and antipathy toward Muslims and immigrants. We examine the interrelated influence of these three factors on Americans' intentions to vote for Trump in 2020. Consistent with previous research, Christian nationalism and Islamophobia remained strong and significant predictors of intention to vote for Trump; however, the effect of xenophobia was stronger. Further, xenophobia and Islamophobia significantly and substantially mediated the effects of Christian nationalism. Consequently, though Christian nationalism remains theoretically and empirically distinct as a cultural framework, its influence on intending to vote for Trump in 2020 is intimately connected to fears about ethnoracial outsiders. In the penultimate year before Trump's reelection campaign, the strongest predictors of supporting Trump, in order of magnitude, were political party, xenophobia, identifying as African American (negative), political ideology, Christian nationalism, and Islamophobia.